2021
DOI: 10.4992/jjpsy.92.20063
|View full text |Cite
|
Sign up to set email alerts
|

The influence of social anxiety, trait anxiety, and perceived vulnerability to disease on the frequency of face mask wearing

Abstract: The purpose of this study was to examine the psychological factors related to the frequency of face mask wearing (mask wearing) among Japanese people. Specifically, the influence of social anxiety (scrutiny fears, social interaction anxiety), trait anxiety, and perceived vulnerability to disease (germ aversion, perceived infectability) on mask wearing frequency was examined. We also investigated whether the relationships were altered based on the COVID-19 pandemic and the seasons. Online surveys (N=6,742) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…First, the hypotheses and main findings of this study are described. It was hypothesized that, for the Japanese people, the trend of inferring emotions accurately from facial expressions would be different than that found in the West, because wearing masks was a common practice in Japan even before the COVID-19 pandemic (Miyazaki et al, 2021 ). In addition, it was predicted that social anxiety and social sensitivity would affect the accuracy of emotion inference from facial expressions when a mask was worn.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the hypotheses and main findings of this study are described. It was hypothesized that, for the Japanese people, the trend of inferring emotions accurately from facial expressions would be different than that found in the West, because wearing masks was a common practice in Japan even before the COVID-19 pandemic (Miyazaki et al, 2021 ). In addition, it was predicted that social anxiety and social sensitivity would affect the accuracy of emotion inference from facial expressions when a mask was worn.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, compared with the effect on the Korean study, the effect of wearing a mask on the current Japanese participants was smaller. Japanese people are used to wearing masks (Miyazaki et al, 2021 ), and they tend to focus on the eyes to infer emotions from others’ facial expressions (e.g., Jack et al, 2009 ; Yuki et al, 2007 ); these descriptions provide insights as to the participants of the current study having potentially been less affected by the presence of a face mask, and that this may be related to Japanese people having prior daily experience of wearing masks and placing a greater focus on eyes for emotion inference. This description, nonetheless, is speculative and warrants further examination in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While in both France and Japan, mask wearing policies or recommendations during the pandemic involved wearing a mask at all times in public spaces and at work, the experience people had with mask wearing prior to the pandemic differed. In Japan, the habit of wearing a mask was widespread before the COVID-19 pandemic ( Chiyoma, 2019 ; Miyazaki et al, 2021 ; Sakakibara and Ozono, 2021 ), and face masks were considered a daily life item. Despite just being encouraged to do so, more than 80% of Japanese people wore a mask during the pandemic ( Ministry of Health, Labour and Welfare, 2020 ), and started doing so early on in the pandemic ( Nakayachi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, there have not been many psychological studies focusing on social trends and the effects of COVID-19. However, if foreign studies are included, such as restrictions on going out and remote work due [ 6 – 8 ], anxiety and coping [ 9 11 ], and discrimination against infected people [ 12 ], fluctuation in intra-family communication and its association with preventive behavior [ 13 15 ], and children who spend more time looking at screens and less time exercising [ 16 18 ]. Several studies have shown that frequent intrafamily communication and parents telling their children about the risk of the virus may promote preventive behaviors within the family [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%